AROMATASE AND NEUROREGENERATION - Ulhaq, Zulvikar Syambani (Malang Neurology Journal, 2019)
Aromatase (cyp19a1) is a converting enzyme for estrogen biosynthesis. A single gene of cyp19a1 identified in mammals and specific promoter differentially regulates E2 produce in the brain.Interestingly, teleost fish having two isoforms of cyp19a1, cyp19a1a and cy19a1b, encoding ovarian and brain aromatase, respectively. In addition, teleost fish are characterized by having highly aromatase activity and neuroregenerative response. In contrast with fish, neuroregeneration process is limited in mammals. Therefore, understanding molecular mechanism of estradiol signaling in neural injury in fish may give a new insight for the development of novel treatment in mammals, particularly in neurodegenerative diseases. Here, the author briefly reviews and discusses the potential role of neural estrogen for regeneration process.